ANALISIS TUTURAN IMPERATIF PADA MEDIA LUAR RUANG DI KABUPATEN SAMBAS: KAJIAN PRAGMATIK - Asrul, Asrul; Muzammil, Ahmad Rabi?ul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study discusses the use of imperative speech in outdoor media in Sambas Regency. Researchers focus on media advertising space and traffic indicators and tourism. The problem in the thesis is the use of imperative speech in outdoor media in Sambas Regency. The purpose of the study is to describe the types and forms of imperative speeches in outdoor media in the Regency. The method used is descriptive method, a form of qualitative research. Source of outdoor media data in Sambas Regency. Data collection techniques documentation and record techniques. Tools for collecting data are cameras, notebooks and stationery. The results of the study there are five types of imperative utterances, namely eighteen ordinary imperative utterances, ten sentences of request orders, two sentences of granting permission, nine sentences of solicitation commands, and two sentences of instructional orders. The imperative speech form consists of two types namely, formal form and imperative pragmatic form. Two forms of formal existence are active imperative and passive imperative. Researcher's further suggestion is that this research can be a reference and reference for the reader regarding the use of imperative speech. Keywords: Pragmatics, Imperatives, Outdoor Media